PENGARUH KOMUNIKASI PEMASARAN TERHADAP PERSEPSI RESIKO, KEPERCAYAAN KONSUMEN, DAN KEPUTUSAN PEMBELIAN PADA ONLINE SHOP (Studi pada Masyarakat Kota Pekanbaru) - Juliati, Raudha; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2016)
This study aimed to analyze the effect of marketing communication on riskperception, consumer trust and purchasing decisions on online shop (studies on society ofPekanbaru City). The sample in this study is the society of Pekanbaru city who ever madepurchasing through online shop for 1 last year and already met the requirements / criterianeeded in filling out the questionnaire, such as age of â¥ 17 years old and at least high schoolgraduates. There were 168 respondents used as samples which were selected by usingincidental sampling technique. The data obtained from this study was further processed byusing AMOS program version 18.The results showed that the variables of marketingcommunications positively and significantly affected risk perception and purchasing decisions,but not significant positive affected consumer trust. Moreover variable of consumer trustsignificantly affected purchasing decisions positively. While the risk perception variablepositively and significantly affected consumer trust, but not significantly affected purchasedecisions.